Homologs of the rolC gene of naturally transgenic toadflaxes Linaria vulgaris and Linaria creticola are expressed in vitro - T. V. Matveeva; O. D. Bogomaz; L. A. Golovanova; Yu. S. Li; D. Dimitrov (Вавиловский журнал генетики и селекции)
Agrobacterium mediated transformation is the most common way for obtaining transgenic plants in laboratory conditions. At the same time, there are species inside the genera Nicotiana, Linaria and Ipomoea that contain homologs of agrobacterial T-DNA genes as a result of genetic transformation of their ancestral forms in natural conditions. Such plants are called naturally transgenic plants, and T-DNA in their genomes is called cellular (cT-DNA). It is proposed that in the evolution of these genera, the introduced sequences played an important role. This idea is confirmed by the data on the expression of some T-DNA genes in Nicotiana and Ipomoea. Until the last moment, the expression of cT-DNA genes in Linaria has not been documented. However, the analysis of the nucleotide sequence indicates the functionality of rolC gene in L. vulgaris Mill., L. acutiloba Fisch. ex Rchb., L. genistifolia (L.) Mill. In this research work, we have sequenced the rolC homolog in one more toadflax species (Linaria creticola Kuprian). The in silico analysis of this gene has shown that it can encode a full-length peptide. Using the real time RT-PCR method, we have demonstrated that the rolC homolog is expressed in vitro in shoots, roots and calli of L. vulgaris Mill., as well as in shoots of L. creticola Kuprian. The results obtained are an important argument in favor of the fact that cT-DNA is functional and that its fixation in genomes played a certain role in the evolutionary process. However, the level of expression of the gene studied is quite low. A similar trend was observed in other naturally transgenic species. This can explain the absence of explicit morphological differences of species containing cT-DNA from their non-transgenic relatives.